2009
DOI: 10.1637/8379-061708-resnote.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Eimeria Species in Broilers with Subclinical Signs from Fifty Farms

Abstract: Understanding the occurrence and distribution of various Eimeria species in broiler farms is necessary to develop effective coccidiosis vaccines. In the current study, fecal samples were collected from broilers with subclinical signs at fifty small-scale farms in the Shandong province in eastern China. Oocysts purified from fecal samples were examined for morphology. The Eimeria genomic DNA extracted from each sample was subjected to PCR amplification with species-specific primers for the internal transcribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 22 publications
2
13
3
Order By: Relevance
“…Mixed infections were associated with small and medium farms and with ionophores. The same findings were observed in China, Shandong province, in small-scale farms where more than one Eimeria species existed in most of the samples [47]. Most likely, the mixed infections are more prevalent in small and medium farms due to poor management and biosecurity practises as high stocking densities, reduced time between successive grow-outs [26], microclimate and workers [22].…”
Section: Discussionsupporting
confidence: 61%
“…Mixed infections were associated with small and medium farms and with ionophores. The same findings were observed in China, Shandong province, in small-scale farms where more than one Eimeria species existed in most of the samples [47]. Most likely, the mixed infections are more prevalent in small and medium farms due to poor management and biosecurity practises as high stocking densities, reduced time between successive grow-outs [26], microclimate and workers [22].…”
Section: Discussionsupporting
confidence: 61%
“…Discrimination of Eimeria species using this technique has sort of limitations to be used as a single tool for diagnosis, meaning that results obtained with this method should be carefully interpreted [ 25 , 26 ]. This is because the measurements of the oocysts may undergo variations due to changes in metabolism of the parasites or birds and even in the value of the shape morphometric indices of the oocysts that may overlap leading to misleading conclusions regarding the species [ 27 ]. Despite the limitations of morphometric techniques, there are some reports that indicated that oocyst morphometry could also be a sensitive method for the discrimination of Eimeria species of poultry in field trials as it shows high degree of agreement with the molecular methods [ 28 – 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCR assays developed by Fornace and colleagues [ 5 ], and Godwin and Morgan [ 15 ] have attempted to address this deficit, although the latter requires equipment that is not currently widely available in many laboratories. Effective detection of circulating Eimeria species is important for proper diagnosis and disease control, and can inform the selection of appropriate anticoccidial drugs and vaccines [ 16 , 17 ]. All seven of the recognised Eimeria species have been detected previously in Nigeria [ 12 ].…”
Section: Introductionmentioning
confidence: 99%